Plasmon‐Enhanced Fluorescence Resonance Energy Transfer. Issue 5 (4th February 2019) - Zong, Huan; Wang, Xinxin; Mu, Xijiao; Wang, Jingang; Sun, Mengtao
Abstract: In this review, we firstly introduce physical mechanism of fluorescence resonance energy transfer (FRET), the methods to measure FRET efficiency, and the applications of FRET. Secondly, we introduce the principle and applications of plasmon‐enhanced fluorescence (PEF). Thirdly, we focused on the principle and applications of plasmon‐enhanced FRET. This review can promote further understanding of FRET and PE‐FRET. Abstract : The physical mechanism and measurement methods of fluorescence resonance energy transfer (FRET) are firstly introduced, and then the principle and applications of plasmon‐enhanced FRET. This review can promote further understanding of FRET and PE‐FRET.